Selective hydrogenation of unsaturated carbonyls by Ni–Fe-based alloy catalysts. Issue 16 (3rd August 2017) - Putro, Wahyu S.; Kojima, Takashi; Hara, Takayoshi; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract : Ni–Fe alloy catalysts prepared by a simple hydrothermal method and subsequent H2 treatment were shown to be highly selective for the hydrogenation of various unsaturated carbonyls. Abstract : Ni–Fe alloy catalysts prepared by a simple hydrothermal method and subsequent H2 treatment exhibited the greatest activity and selectivity for the hydrogenation of biomass-derived furfural to furfuryl alcohol among the examined second metals, such as Al, Ga, In, Co, and Ti. This work reveals that the alloying of Ni and Fe is a key factor in achieving highly selective hydrogenation of the CO moiety in unsaturated carbonyl substrates. We found that decreasing the temperature of H2 treatment ( i.e. decreasing the crystallite size), e.g. Ni–Fe(2)HT-573 K (TOF = 952 h −1 ), increased the activity compared to that over Ni–Fe(2)HT-673 (TOF = 375 h −1 ) for furfural hydrogenation. This result suggests that a low-coordinated Ni–Fe alloy was imperative for the catalytic cycle. Moreover, the effect of the metal/support interface was critical; despite the high catalytic performance of Ni–Fe/TiO2, Ni–Fe/Al2 O3, and Ni–Fe/CeO2, Ni–Fe supported on SiO2, taeniolite, and hydrotalcite catalysts were ineffective. Vibrational studies using FT-IR measurement confirmed that furfural was physically adsorbed on the surface of the Ni–Fe alloy catalyst via an η 1 (O) configuration. The synthetic scope of the Ni–Fe catalytic system was very broad; various types of unsaturated carbonyls, such as unsaturated aromatics, unconjugated aliphatics, and a large substituent, were selectively converted into the corresponding unsaturated alcohols.